Comparative analysis of managerial pratices in small medium enterprises in Malaysia - Abdul Hamid, Abu Bakar; Baharun, Rohaizat; Hashim, Noor Hazarina (Fakulti Pengurusan dan Pembangunan Sumber Manusia, 2006)
The purpose of this paper is to examine the existing practice in managerial strategic and tools being used and problems faced by local small medium enterprises (SMEs) in the manufacturing sector. With today’s arduous competition, it requires the SMEs to tune its current business practice to cope with the rapid changes in the business environment. Due to the rapid changes, SMEs’ managers need to equip themselves with new knowledge and ideas to promote effective managerial practices. In other word, SMEs must have better trained managers, knowledgeable in managerial activities. Focus should be on the knowledge on financial management, human resource management and marketing management techniques. The research method was adopted from the combination of quantitative and qualitative approaches. Since there is no detailed and up-to-date databases about SMEs in the Malaysian industry, the sampling plan was designed by using judgment and snowball sampling. A total of 102 responses were obtained from the owner-managers drawn from Johor Bahru city area. The most important findings of the study on managerial practices are that the SMEs appear to have a very limited knowledge of the overall spectrum of managerial practices.